衔愁寻觅旧游踪：论南来文人许建吾 歌词中的家国之思: Looking for the Ancient Path with Sorrow: Thoughts of Home and Country in Southbound Literatus Hsu Chien Wu’s lyrics - Lim Ka Ling 林嘉玲 (Journal of Sinological Studies 漢學研究學刊, 2024)
许建吾（1903—1987）是20世纪著名的现代诗人与歌词作家。一生漂泊的生命轨迹，南京、香港、新马及台湾等地都遗留着他对当地音乐文教的贡献，而歌词承载着许建吾在不同地域之间的心境变化。许建吾的歌词创作具有多元面向，从军歌战词到抒情艺术歌曲皆有涉猎。然而，许建吾至今较少受到学界关注，现有研究多止于其生平事迹与作品的搜集整理，且相关论述长期以来主要来自音乐界，文学领域对其歌词的探讨仍属阙如。有鉴于此，本文尝试以许建吾的歌词为研究材料，首先探讨其在中国国内所受军中文艺环境下的创作养成；继而分析其旅居海外时南来北往的离散经验如何影响其思想基调，藉此呈现许建吾作为“南来文人”在动荡年代中的家国之思。 The study focuses on the lyrics of Hsu Chien Wu (1903-1987), a famous modern poet and lyricist in the 20th century. Throughout his wandering life, he made enduring contributions to local music, literature, and education in cities such as Nanjing, Hong Kong, Singapore, Malaysia, and Taiwan. His lyrics serve as an expressive medium that captures the emotional shifts he experienced across these diverse geographical and political landscapes. Hsu’s lyric creations are marked by their stylistic diversity, ranging from martial anthems to lyrical art songs. However, Hsu has received limited scholarly attention. Existing research has largely focused on biographical documentation and the collection of works, with most discussions originating from the field of music studies, while literary analyses of his lyrics remain scarce. In light of this gap, this paper focuses on Hsu’s lyrics as primary material. It first examines how his early creative development was shaped by the military literary environment in China, and then analyzes how his diasporic experiences during his time abroad informed the ideological tone of his works, aiming to reveal Hsu Chien Wu’s thoughts of home and country as a “Southbound Literatus” in the turbulent years.